Information and communication technology (ICT) adoption and community: a systematic literature review - Rohani Hasbie, Siti Nur; Adam Assim, Mohamad Ibrani Shahrimin; Taasim, Shairilizwan; Anuar, Faizul Nizar (Human Resource Management Academic Research Society, 2023)
Information and communication technology (ICT) is one of the field of studies that is often discussed by almost all communities globally. ICT in community life and its role in providing conducive environment has been pertinently examined by researchers worldwide. This systematic literature review (SLR) reviews the community aspects of ICT adoption. The review processes included five key methodological steps, namely guided by protocol review, formulating the research questions, systematic advance searching strategies based on identification, screening and eligibility adopted from PRISMA, and several databases which included Science Direct and Scopus, followed by quality appraisal and data extraction from the journal articles and lastly, the analyses. Thematic analysis were conducted and five main themes were discovered: (1) technology assisted; (2) livelihood diversity; (3) innovation; (4) government and organization support and policies and (5) social related. The findings show that every element of community life has been impacted by the use of ICT, including daily routines, workplace operations, communication channels, rising levels of workplace innovation, online transactions, and a direct improvement in the standard of living around the globe.